Combined inhalation of beta2‐agonists improves swim ergometer sprint performance but not high‐intensity swim performance. Issue 5 (9th July 2013) - Kalsen, A.; Hostrup, M.; Bangsbo, J.; Backer, V.
<x xml:space="preserve">Abstract</x> There is a high prevalence of asthma and airway hyperresponsiveness (AHR) in elite athletes, which leads to a major use of beta2‐agonists. In a randomized double‐blinded crossover study, we investigated the effects of combined inhalation of beta2‐agonists (salbutamol, formoterol, and salmeterol), in permitted doses within the World Anti‐Doping Agency 2013 prohibited list, in elite swimmers with (AHR, n = 13) or without (non‐AHR, n = 17) AHR. Maximal voluntary isometric contraction of m. quadriceps (MVC), sprint performance on a swim ergometer and performance in an exhaustive swim test at 110% of VO2max were determined. Venous plasma interleukin‐6 (IL‐6) and interleukin‐8 (IL‐8) were measured post‐exercise. No improvement was observed in the exhaustive swim test, but swim ergometer sprint time was improved (P < 0.05) in both groups from 57 ± 1.7 to 56 ± 1.8 s in AHR and 58.3 ± 1 to 57.4 ± 1 s in non‐AHR. MVC and post‐exercise plasma IL‐6 increased (P < 0.05) with beta2‐agonists in both groups, whereas IL‐8 only increased in AHR. In summary, inhalation of beta2‐agonists, in permitted doses, did not improve swim performance in elite swimmers. However, swim ergometer sprint performance and MVC were increased, which should be considered when making future anti‐doping regulations.